Implication of customer and entrepreneurial orientations for Malay SME performance in Selangor / Zetty Akhtar Shafinaz Saleh - Saleh, Zetty Akhtar Shafinaz (2014)
This research is focused on the Malay Small and Medium Enterprise (SME) performance in Selangor. In background of study, this research will discuss about dependent and independent variables. Dependent variable in this study is Malay SME performance and the independent variables are the implication of customer orientation and entrepreneurial orientation. This paper will discuss the gap of the problem in the research in problem statement.